The changing role of Japanese NGOs :|a case study of a Japanese NGO in Turkey - Gündüz, Melisa. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The aim of this thesis is to present the late, yet steady development of Japanese humanitarian non-governmental organizations (NGOs) in the sector of global humanitarian aid by focusing on one international Japanese humanitarian aid NGO, the Association for Aid and Relief Japan, and its operation in the Syrian refugee response in Turkey. In this context, the study provides a general framework of the late development of the Japanese humanitarian aid through NGOs from the post-war period until the current day, highlighting the parallelism in their contemporary place both in overseas operations and government. Furthermore, the study will discuss the ongoing growth of their operations within the main matter in question and draw on the field operation of the AARJ within the scope of their steady and sturdy growth. Along with the desolate continuity of man-made crises, and the rise of unpredictable environmental crises, the visible growth of humanitarian aid through NGOs has gained a greater value and place within the global governance systems as one of the most practical and efficient response mechanisms. Therefore, by examining the real time field experience of the AARJ and its donor relations, this thesis offers the opportunity to thoroughly perceive the potential and possibilities in relation to the future of Japanese humanitarian aid NGOs.
Keywords: Non-governmental organizations -- Japan.; Refugees, Syrian -- Turkey.